1992
DOI: 10.1002/ajh.2830400312
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous remission of multilobated non‐Hodgkin lymphoma

Abstract: A 67-year-old previously well man was admitted with hypercalcemia after a 7-day history of fever, night sweats, and back pain. The blood showed 5% multilobated lymphoid cells. A multilobated non-Hodgkin lymphoma associated with marked reticulin fibrosis was diagnosed on a bone marrow biopsy. During the next 7 days, in the absence of specific therapy, his symptoms disappeared. Three weeks after admission his biochemical abnormalities had resolved and after 9 weeks his bone marrow examination was normal. He rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Although spontaneous regression ( SR) in patients with low-grade lymphoma has been reported to occur in 5 to 15 percents of patients 1,2 , aggressive non-Hodgkin's lymphoma (NHL) cases showing SR are extremely rare [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . We report here a case of diffuse large B cell lymphoma (DLBCL) harboring Epstein-Barr virus (EBV) that showed SR in the absence of any anti-neoplastic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although spontaneous regression ( SR) in patients with low-grade lymphoma has been reported to occur in 5 to 15 percents of patients 1,2 , aggressive non-Hodgkin's lymphoma (NHL) cases showing SR are extremely rare [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . We report here a case of diffuse large B cell lymphoma (DLBCL) harboring Epstein-Barr virus (EBV) that showed SR in the absence of any anti-neoplastic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Three case reports also describe complete spontaneous remissions of highly malignant lymphomas. Poppema et al [9] observed the remission of a lymphoblastic lymphoma in a 12-year-old boy, and Grigg et al [10] reported on a 67-year-old man with NHL. Furthermore Grem et al [11] describe a case where FIGURE 6 Mucous membrane finding in region 037-038 from November 14, 2000: regressive mucous membrane finding.…”
Section: Discussionmentioning
confidence: 97%
“…During the dramatic advances in histology in the area of lymphoma from 1970 to 1990, many concerns about multilobated B-cell lymphoma were declared although most of the clinicopathological studies of multilobated B-cell lymphoma described a relatively good prognosis in the CHOP era. [12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Few additional reports about ml-DLBCL have appeared afterward. Exceptionally, Shimano et al 39 reported a poor prognosis group of DLBCL with a polyploid chromosomal abnormality that showed histological findings of Hodgkin's-like giant and multilobated cells.…”
Section: Discussionmentioning
confidence: 99%
“…During the dramatic advances in histology in the area of lymphoma from 1970 to 1990, many concerns about multilobated B‐cell lymphoma were declared although most of the clinicopathological studies of multilobated B‐cell lymphoma described a relatively good prognosis in the CHOP era 12–14,16–29 . Few additional reports about ml‐DLBCL have appeared afterward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation